A Gel‐Free Ti3C2Tx‐Based Electrode Array for High‐Density, High‐Resolution Surface Electromyography. Issue 8 (21st June 2020) - Murphy, Brendan B.; Mulcahey, Patrick J.; Driscoll, Nicolette; Richardson, Andrew G.; Robbins, Gregory T.; Apollo, Nicholas V.; Maleski, Kathleen; Lucas, Timothy H.; Gogotsi, Yury; Dillingham, Timothy; Vitale, Flavia
Abstract: Wearable sensors for surface electromyography (EMG) are composed of single‐ to few‐channel large‐area contacts, which exhibit high interfacial impedance and require conductive gels or adhesives to record high‐fidelity signals. These devices are also limited in their ability to record activation across large muscle groups due to poor spatial coverage. To address these challenges, a novel high‐density EMG array is developed based on titanium carbide (Ti3 C2 T x ) MXene encapsulated in parylene‐C. Ti3 C2 T x is a 2D nanomaterial with excellent electrical, electrochemical, and mechanical properties, which forms colloidally stable aqueous dispersions, enabling safe, scalable solutions‐processing. Leveraging the excellent combination of metallic conductivity, high pseudocapacitance, and ease of processability of Ti3 C2 T x MXene, the fabrication of gel‐free, high‐density EMG arrays is demonstrated, which are ≈8 µm thick, feature 16 recording channels, and are highly skin conformable. The impedance of Ti3 C2 T x electrodes in contact with human skin is 100–1000× lower than the impedance of commercially available electrodes which require conductive gels to be effective. Furthermore, the arrays can record high‐fidelity, low‐noise EMG, and can resolve muscle activation with improved spatiotemporal resolution and sensitivity compared to conventional gelled electrodes. Overall, the results establish Ti3 C2 T x ‐based bioelectronic interfaces as a powerful platform technology for high‐resolution, noninvasive wearable sensing technologies. Abstract : High‐fidelity, high‐resolution recording of muscle activity from the skin surface is made possible using gel‐free Ti3 C2 T x MXene contacts patterned into flexible, high‐density surface electromyography arrays. Completed devices, fabricated using scalable solution‐processing techniques and biocompatible polymeric substrates, enable tracking muscle activation and coordination across space and time in small and large muscle groups with improved quality and sensitivity over clinical standards.